2017
DOI: 10.1111/hae.13364
|View full text |Cite
|
Sign up to set email alerts
|

Use of telehealth in the delivery of comprehensive care for patients with haemophilia and other inherited bleeding disorders

Abstract: Advances in technology such as telemedicine (TM) have made access to cost-effective, quality health care feasible for remote patients. TM is especially well suited for patients with chronic disorders such as haemophilia and related haemostatic disorders that benefit not only from more frequent interaction with care providers at a specialized haemophilia treatment center but also from consultations with other specialists. Telehealth refers to a broader application of TM and includes non-clinical services such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…[18][19][20][21] In a recent study, the use of an app improved the adherence measured with the VERITAS-Pro scale, quality of life and illness perception after 1 year. 22 Several experiences of telehealth in haemophilia have been reported, 23 including an interesting experience of telemedicine by videoconference in paediatric patients. 24 The results of our survey highlight the preference for apps, and we are implementing the employment of a specific app for recording infusions and bleed-related occurrences.…”
Section: Pro Scale (Validated Haemophilia Regimen Treatment Adherencementioning
confidence: 99%
“…[18][19][20][21] In a recent study, the use of an app improved the adherence measured with the VERITAS-Pro scale, quality of life and illness perception after 1 year. 22 Several experiences of telehealth in haemophilia have been reported, 23 including an interesting experience of telemedicine by videoconference in paediatric patients. 24 The results of our survey highlight the preference for apps, and we are implementing the employment of a specific app for recording infusions and bleed-related occurrences.…”
Section: Pro Scale (Validated Haemophilia Regimen Treatment Adherencementioning
confidence: 99%
“…Compared to the previous survey there was a marked increase in those identifying geographical access as a technical assistance need. Subsequently, one of four projects of national significance funded by the NHPCC evaluated how HTCs could provide care remotely to rural areas using telemedicine 8 . The pilot study demonstrated a high level of patient satisfaction with the telemedicine approach and significant cost savings, both in terms of cost of travel and time away from work.…”
mentioning
confidence: 99%
“…The pilot study demonstrated a high level of patient satisfaction with the telemedicine approach and significant cost savings, both in terms of cost of travel and time away from work. While telemedicine outreach clinics have long existed and been utilized in a Accepted Article number of HTCs to resolve geographical access challenges the pilot project results published in 2018 demonstrated that, while not without challenges, telemedicine is especially well-suited for patient s with chronic disorders such as hemophilia 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tools that may improve comprehensive care and transition include telemedicine and mobile health technology (mHealth). Some Hemophilia Treatment Centers (HTCs) are incorporating telehealth to reach patients who live at a distance from the HTC and/or to supplement education provided at annual comprehensive visits. mHealth may be used to track outcomes such as activity and medication adherence.…”
Section: Why Do We Need To Train Clinical Specialists In Hemostasis Amentioning
confidence: 99%